Diazepam Potentiates the Antidiabetic, Antistress and Anxiolytic Activities of Metformin in Type-2 Diabetes Mellitus with Cooccurring Stress in Experimental Animals - Garabadu, Debapriya; Krishnamurthy, Sairam (Hindawi Publishing Corporation, 2014)
Psychological stress is considered as one of the limiting factors in the management of type-2 diabetes mellitus (T2DM). Therefore, the basic objective of the present study was to evaluate the antidiabetic effect of metformin, diazepam, and their combination in cooccurring T2DM and stress condition (DMS). T2DM was induced in the male rats by administering streptozotocin (45 mg/kg, i.p.) and nicotinamide (110 mg/kg, i.p.) with time lag of 15 min. Rats were subjected to two sessions of cold restraint stress paradigm for one hour on the sixth and seventh day after streptozotocin injection. Administration of metformin (25 mg/kg, p.o.) and diazepam (1 mg/kg, p.o.) in combination from the seventh to thirteenth day after streptozotocin injection showed better improvement in glucose tolerance and insulin sensitivity compared to monotherapy of either drug. In addition, the combination significantly attenuated DMS-induced hyperglycemia, hypertriglyceridaemia, hypercorticosteronemia, anxiety-like behavior, and insulin resistance through modulating insulin signaling pathway in the liver compared to monotherapy. Further, improvement of mitochondrial function, integrity, and oxidative stress in hippocampus, hypothalamus, prefrontal cortex, striatum, amygdala, and nucleus accumbens was observed with the combination. Therefore, metformin in combination with diazepam may be a better therapeutic option in the management of T2DM with cooccurring stress condition.
Keywords: diazepam; nicotinamide; matrix metalloproteinase; streptozotocin-induced diabetes mellitus